Presence of Multiple Autoimmune Antibodies Involved in Concurrent Myositis and Myocarditis and Myasthenia Gravis Without Thymoma: A Case Report - Zhou, Zhijian; Chen, Xia; Liu, Gonglu; Pu, Jiali; Wu, Jimin (Frontiers in Neurology, 2019)
Inflammatory myositis (IM) and myasthenia gravis (MG) are both immune disorders involving muscle. The concurrent presence of both conditions in the same patient is extremely rare and the diagnosis is important and challenging. Here, we report a case of concurrent myositis and myocarditis and MG without thymoma in a 69-year-old man with progressive proximal muscle weakness and dysphagia. As an atypical finding, the laboratory immunity assay showed the presence of multiple antibodies (acetylcholine receptor-Ab, titin-Ab, M7-Ab, smooth muscle alpha (SMA)-Ab and citrate acid extract (CAE)-Ab). We predicted that thymoma-associated antibodies (titin-Ab, SMA-Ab and CAE-Ab) and anti-M7 antibodies play an important role in the concurrent presence of MG and myositis and myocarditis. In this overlap case, immunotherapy was determined to be effective.